Understanding phage BX-1 resistance in Vibrio alginolyticus AP-1 and the role of quorum-sensing regulation - Xiaoyu Li; Xin Liu; Tianyi Ma; Haochen Su; Bingrui Sui; Lili Wang; Bilal Murtaza; Yongping Xu; Na Li; Demeng Tan (Microbiology Spectrum)
ABSTRACT The marine ecosystem is characterized by a rich diversity of bacterial hosts and their phages. The propagation of phages is primarily limited by their ability to adsorb to host cells and is further challenged by various bacterial defense mechanisms. To fully realize the potential of phage therapy in aquaculture, a comprehensive understanding of phage-host interactions and their regulation is essential. In this study, we isolated a novel Myoviridae phage, BX-1, capable of infecting Vibrio alginolyticus AP-1, and characterized its resistant mutants. We elucidated the essential role of the bacterial cellulose biosynthesis-related gene bcsE, which functions as a cyclic di-GMP-binding protein, in influencing host susceptibility to phage BX-1. Interestingly, Congo Red, Calcofluor White staining, and cellulose content assays indicated that deletion of bcsE in strain AP-1 does not completely abolish cellulose production, suggesting that bcsE is not essential for bacterial cellulose synthesis. Furthermore, investigating the signaling molecules that regulate phage-host interactions, we find that in a high cell density state (ΔluxO), bacterial cells upregulate their susceptibility to phage BX-1, which leads to a rapid development of resistance. Conversely, cells in a low-density state (ΔhapR) exhibit reduced susceptibility to phage BX-1 while still producing comparable phage progenies. This population density-dependent response is primarily enhanced by the predicted quorum-sensing autoinducer CAI-1, synthesized by the gene cqsA. Collectively, our findings reveal the intricate dynamics of phage-host interactions, adding a new layer of complexity to our understanding of phage receptor regulations.IMPORTANCEPhage therapy has garnered significant attention as a promising solution to antibiotic resistance in aquaculture. However, its application is hindered by a limited understanding of the genotypic and phenotypic dynamics governing phage-host interactions. Bacteria have developed various defense mechanisms against phages, such as mutations in phage receptors. In this study, we demonstrate that the bacterial cellulose biosynthesis-related gene bcsE plays a crucial role in determining susceptibility to phage BX-1, while quorum-sensing (QS) systems significantly influence collective phage-related behaviors. By characterizing the mechanisms of phage resistance and the regulatory role of QS in susceptibility, our findings enhance the understanding of phage-host interactions and pave the way for more effective phage therapy applications. Collectively, these insights illuminate the evolutionary complexities of phage-defense systems and the broader strategies that bacteria employ to coexist with phages.